Correlations of Serum Vitamin D and Thyroid Hormones with Other Biochemical Parameters in Iraqi Pregnant Women with Preeclampsia Disease - Namir I.A. Haddad (Journal of Global Pharma Technology, 2019)
Objectives: Preeclampsia is disorder of hypertension in the second half of pregnancy. This study aimed to find correlation of preeclampsia with Vitamin D, thyroid hormones and other parameters in Iraqi pregnant women. Methods: Case study of fifty-eight pregnant with preeclampsia (twenty-nine pregnant women with mild preeclampsia, and twenty-nine pregnant with sever preeclampsia) and twenty-nine healthy pregnant in third trimester was included this study. Serum of Vitamin D, TSH, T3, T4 and other biochemical parameters were measured. Results: The results showed significant decrease (P<0.001) in serum T3 and T4 in mild and sever preeclampsia groups compared to healthy group (1.31±0.31ng/ml and 1.32±0.15ng/ml vs.1.53±0.26ng/ml) and (7.65±0.73µg/dl and 7.40±0.85µg/dl vs. 8.953±0.66µg/dl) respectively. Serum TSH showed significant increase (P<0.001) in mild and sever preeclampsia groups in comparison to healthy group (2.76±0.76µIU/ml and 3.81±0.94µIU/ml vs. 2.43±0.64µIU/ml) respectively. Also, significant decrease in serum vitamin D in mild and sever preeclampsia groups in comparison to healthy group (9.152±1.03ng/ml and 8.564±1.67ng/ml vs. 21.992±5.59ng/ml) respectively. Conclusion: Our results found positive correlation between T3 level with age (P=0.033), gravidity (P=0.024) and history of abortion (P=0.002). Positive correlation T4 level with BMI (P=0.021), gravidity (P=0.040), parity (P=0.039), while a negative correlation with family history (P=0.003) was found. Level Vit.D had positive correlation with gravidity (P = 0.044) and parity (P=0.019), although no correlation found between thyroid hormones and Vit.D during the 3rd trimester. Also, levels TSH, T3, T4 and Vitamin D can be used to predict the severity of PE.Keywords: Vitamin D, TSH, T3, T4, Preeclampsia, Mild PE, Sever PE.